2018
DOI: 10.1556/446.14.2018.s1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ripening temperature on the texture of cow milk Kashkaval cheese

Abstract: Texture development during ripening of cow milk Kashkaval cheese at different temperatures (9±1 °С, 11±1 °С and 13±1 °С) was studied. Texture parameters representing cheese hardness, cohesiveness, springiness, adhesiveness, gumminess and chewiness were determined by texture profile analysis. It was found that hardness, gumminess and adhesiveness of all studied samples increased, while springiness and cohesiveness decreased during ripening. An increase of chewiness values during the first stages of ripening was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Surprisingly, and contrary to the findings of Kanawjia et al [ 28 ], we noticed a downward trend with ripening time for both CC (from 0.46 to 0.24) and LC (from 0.44 to 0.24). Nevertheless, Ivanov et al [ 29 ] reported changes in the cohesiveness of Kashkaval cheese during ripening, like those we observed, being attributed to proteolysis.…”
Section: Resultssupporting
confidence: 74%
“…Surprisingly, and contrary to the findings of Kanawjia et al [ 28 ], we noticed a downward trend with ripening time for both CC (from 0.46 to 0.24) and LC (from 0.44 to 0.24). Nevertheless, Ivanov et al [ 29 ] reported changes in the cohesiveness of Kashkaval cheese during ripening, like those we observed, being attributed to proteolysis.…”
Section: Resultssupporting
confidence: 74%